Continuous Training Program: Strategic Innovation for Optimizing Teacher Professionalism - Handiko, Qowi; Kardoyo, Kardoyo; Widiyanto, Widiyanto; Masrukhi, Masrukhi (Proceedings of International Conference on Science, Education, and Technology, 2024)
This article discusses the crucial role of Continuous Training Programs as a strategic innovation to optimize the professionalism of teachers in Indonesia. Teachers play a central role in shaping the future of education and student development, making the quality of education heavily dependent on their abilities and qualifications. Continuous Training Programs become a key solution in enhancing the competence and qualifications of teachers, ensuring they remain relevant in the face of constant changes in the education world. This article examines the essential elements of Continuous Training Programs, including the use of technology for interactive learning, mentoring, and additional skill development. Additionally, the article highlights the importance of continuous evaluation and monitoring to measure the impact of training programs on teaching quality. Continuous Training Programs can also serve as a means of professional recognition and incentives, encouraging teacher participation in these programs. This research is a qualitative descriptive study related to Continuous Training Programs for Teachers through documentation and literature studies. By implementing effective Continuous Training Programs, teachers in Indonesia can continue to enhance their competence, making teaching more innovative, and actively contributing to positive transformations in the education system. This program will not only benefit teachers but also bring significant positive impacts on the overall quality of education in Indonesia